trans-Zeatin-N-glucosides have biological activity in Arabidopsis thaliana - Hallmark, H Tucker; Černý, Martin; Brzobohatý, Břetislav; Rashotte, Aaron M (PloS one, 2020)
Cytokinin is an indispensable phytohormone responsible for physiological processes ranging from root development to leaf senescence. The term "cytokinin" refers to several dozen adenine-derived compounds occurring naturally in plants. Cytokinins (CKs) can be divided into various classes and forms; base forms are generally considered to be active while highly abundant cytokinin-N-glucosides (CKNGs), composed of a CK base irreversibly conjugated to a glucose molecule, are considered inactive. However, results from early CK studies suggest CKNGs do not always lack activity despite the perpetuation over several decades in the literature that they are inactive. Here we show that exogenous application of trans-Zeatin-N-glucosides (tZNGs, a specific class of CKNGs) to Arabidopsis results in CK response comparable to the application of an active CK base. These results are most apparent in senescence assays where both a CK base (tZ) and tZNGs (tZ7G, tZ9G) delay senescence in cotyledons. Further experiments involving root growth and shoot regeneration revealed tZNGs do not always have the same effects as tZ, and have largely distinct effects on the transcriptome and proteome. These data are in contrast to previous reports of CKNGs being inactive and raise questions about the function of these compounds as well as their mechanism of action.
Keywords: Arabidopsis; zeatin; cytokininy; kořeny rostlin; glukosidy; Plant Growth Regulators; Glucosides; Plant Roots; regulátory růstu rostlin; Zeatin; Cytokinins